1995
DOI: 10.1038/bjc.1995.198
|View full text |Cite
|
Sign up to set email alerts
|

Do DNA ploidy and S-phase fraction in primary tumour predict the response to chemotherapy in metastatic breast cancer?

Abstract: The relationship between the response to chemotherapy with cyclophosphamide, epirubicin and fluorouracil as well as the time to progression of metastasised breast cancer and DNA ploidy and S-phase fraction (SPF) of primary tumours was examined using paraffin-embedded tumour tissue from 81 patients. The response to chemotherapy was significantly better in patients with tumours with a high SPF, and in addition the time to progression was longer in the high-SPF group. There was no significant difference when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Studies on breast cancer have shown that patients whose primary tumour has high proliferative activity respond better to CT (Remvikos et al, 1989;O'Reilly et al, 1992;Hietanen et al, 1995). Similar results have been obtained in a melanoma study (Karlsson et al, 1996).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Studies on breast cancer have shown that patients whose primary tumour has high proliferative activity respond better to CT (Remvikos et al, 1989;O'Reilly et al, 1992;Hietanen et al, 1995). Similar results have been obtained in a melanoma study (Karlsson et al, 1996).…”
supporting
confidence: 75%
“…However, little is known about tumour-related factors which might predict CT response in STS. In several other tumours a high proliferation rate has been shown to be one of the factors increasing responsiveness to CT (Mattern et al, 1986;Remvikos et al, 1989;O'Reilly et al, 1992;Hietanen et al, 1995).…”
mentioning
confidence: 99%
“…The response to chemotherapy was significantly better in patients with tumours with a high SPF (Hietanen et al, 1995). Surprisingly, low-grade tumours responded better (Niskanen et al, 1997).…”
mentioning
confidence: 90%
“…Both ductal and lobular carcinomas were histologically graded by one pathologist (KF) according to the Richardson Bloom classification modified by Elston and Ellis (1991). The cutoff point for low and high SPF was 4.2% in diploid tumours and 12.5% in aneuploid tumours (Hietanen et al, 1995), which is the median of the respective groups in a large series of SPF determination in our laboratory. p53 immunohistochemical assays were performed using the D07 (Novocastra) antibody, and we interpreted the tumour as positive for p53 overexpression if > 10% of cells stained positively.…”
Section: Materials and Methods Patients And Tumour Materialsmentioning
confidence: 99%
See 1 more Smart Citation